2016
DOI: 10.1186/s12905-016-0353-z
|View full text |Cite
|
Sign up to set email alerts
|

Vision-related quality of life and psychological status in Chinese women with Sjogren’s syndrome dry eye: a case-control study

Abstract: BackgroundSjogren’s syndrome dry eye (SSDE) mainly affects middle-aged women and can negatively affect women’s psychological and social functioning. However, little is known about the correlation between vision-related quality of life (VR-QoL) and psychological status for women with SSDE. We therefore examined VR-QoL and psychological status in two groups of Chinese women: an SSDE group and a non-SSDE group. We also explored the associations between VR-QoL scores, sociodemographic measures, ophthalmologic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Depression as a comorbidity of DED has been described extensively, including in three systematic reviews and metaanalyses. 2,3,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] This is an important point, since depression is closely associated with sleep disorders. 72,73 Zheng et al 3 reviewed the literature and reported that the highest prevalence of depression among ophthalmic patients was in those with DED (29%), followed by glaucoma (25%), age-related macular degeneration (24%), and cataract (23%), evaluated with the Beck Depression Inventory, Center for Epidemiologic Studies Depression Scale, and HADS.…”
Section: Patients With Ded Are Depressivementioning
confidence: 99%
“…Depression as a comorbidity of DED has been described extensively, including in three systematic reviews and metaanalyses. 2,3,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] This is an important point, since depression is closely associated with sleep disorders. 72,73 Zheng et al 3 reviewed the literature and reported that the highest prevalence of depression among ophthalmic patients was in those with DED (29%), followed by glaucoma (25%), age-related macular degeneration (24%), and cataract (23%), evaluated with the Beck Depression Inventory, Center for Epidemiologic Studies Depression Scale, and HADS.…”
Section: Patients With Ded Are Depressivementioning
confidence: 99%
“… 4 Meanwhile, EP is a symptom of dry eye, and many previous studies have demonstrated that dry eye patients have accompanying psychological disorders such as anxiety and depressive symptoms as a result of chronic EP. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…23,[32][33][34][35] A meta-analysis of 22 published studies showed increased odds ratio for depression and anxiety in patients with ocular Sjögren syndrome (SS). 36 There is increased evidence that dry eye is an inflammatory disease, and this review will focus on matrix metalloproteinases (MMPs) and their role in the pathogenesis of dry eye.…”
Section: Dry Eye Overviewmentioning
confidence: 99%
“…24,25 Dry eye causes corneal irregularity [26][27][28] and decreases functional vision by altering contrast sensitivity [29][30][31] and, therefore, decreases quality of life with a significant burden on the individual as well as the society. 23,[32][33][34][35] A meta-analysis of 22 published studies showed increased odds ratio for depression and anxiety in patients with ocular Sjögren syndrome (SS). 36 There is increased evidence that dry eye is an inflammatory disease, and this review will focus on matrix metalloproteinases (MMPs) and their role in the pathogenesis of dry eye.…”
mentioning
confidence: 99%